Pemamfaatan Media Sosial sebagai Sarana Informasi Mengenai Kemudahan Berinvestasi Selama Covid 19 - Ibnu Syawali Manurung; M. Aldiran Oktofa (STIT Sirojul Falah Bogor, 2023)
There is a lot of information that can be accessed through telecommunication media and internet media which we can access easily through our gadgets/smarphones, there is a lot of information about investments circulating on social media about the ease and safety of investing. Investment is one of the strategies used by the community to manage finances, which has been known for a long time as an effort to ensure the availability of funds when needed. Investments or savings are made by all people who have a business or do not have a business such as private employees who do not have a steady income, or who have a fixed income. This study aims to find out how much information we can get from social media about the ease of investing so that every community can find out what and how to invest easily, especially in terms of perceived benefits, perceived convenience, and perceptions of trust in sources of information received for validating the information, the rise of cases. This research uses qualitative methods in which reference sources are taken. from journals of previous people and the results of interviews with people in the city of Medan as a sample Keyword : information, investment, convenience